Gene polymorphisms in pattern recognition receptors and susceptibility to idiopathic recurrent vulvovaginal candidiasis - Rosentul, Diana C.; Delsing, Corine E.; Jaeger, Martin; Plantinga, Theo S.; Oosting, Marije; Costantini, Irene; Venselaar, Hanka; Joosten, Leo A. B.; van der Meer, Jos W. M.; Dupont, Bertrand; Kullberg, Bart-Jan; Sobel, Jack D.; et al. (Frontiers in Microbiology, 2014)
Objective. Approximately 5% of women suffer from recurrent vulvovaginal candidiasis (RVVC). It has been hypothesized that genetic factors play an important role in the susceptibility to RVVC. The aim of this study was to assess the effect of genetic variants of genes encoding for Pattern Recognition Receptors (PRRs) on susceptibility to RVVC. Study design. For the study, 119 RVVC patients and 263 healthy controls were recruited. Prevalence of polymorphisms in five PRRs involved in recognition of Candida were investigated in patients and controls. In silico and functional studies were performed to assess their functional effects. Results. Single nucleotide polymorphisms (SNPs) in TLR1, TLR4, CLEC7A and CARD9 did not affect the susceptibility to RVVC. In contrast, a non-synonymous polymorphism in TLR2 (rs5743704, Pro631His) increased the susceptibility to RVVC almost 3-fold. Furthermore, the TLR2 rs5743704 SNP had deleterious effects on protein function as assessed by in-silico analysis, and in-vitro functional assays suggested that it reduces production of IL-17 and IFN upon stimulation of peripheral blood mononuclear cells with C. albicans. No effects were observed on serum MBL concentrations. Conclusion. Genetic variation in TLR2 may significantly enhance susceptibility to RVVC by modulating host defense mechanisms against Candida. Additional studies are warranted to assess systematically the role of host genetic variation for susceptibility to RVVC.